THE ROLE OF TRANSFORMATIONAL LEADERSHIP STYLE IN PSYCHOLOGICAL EMPOWERMENT OF EMPLOYEES: LITERATURE REVIEW - Egi Vizya Adri; Dedi Setiawan; Chandra Alfian F. Hia (Indonesian Journal of Multidisciplinary Science, 2022)
Leadership is closely related to the existing human resources in the organization as a key success factor. Therefore, companies need skilled leaders, who can serve as role models for their subordinates, and are able to make changes for the better in the future. The importance of employees in determining the success of the organization, the company pays attention to performance constraints. This study aims to examine the role of transformational leadership style on employee psychological empowerment. This type of research uses a literature review with secondary data. The data is obtained through a search on Google Scholar with the search limited from 2016 to 2022 which can be accessed in full text. The role of transformational leadership style on employee psychological empowerment can be applied. Leaders with this leadership style can provide encouragement to employees in their psychological empowerment. So that leadership has a significant influence on the psychology and welfare of its employees. Through empowerment, it will motivate employees to participate more in the company's internal decision making, thereby increasing the sense of responsibility and improving performance, which also affects employees and increases employee job satisfaction